Altered Regulation of the Glucose Transporter GLUT3 in PRDX1 Null Cells Caused Hypersensitivity to Arsenite - Reem Ali (9913494) (2023)
Targeting tumour metabolism through glucose transporters is an attractive approach. However, the role these transporters play through interaction with other signalling proteins is not yet defined. The glucose transporter SLC2A3 (GLUT3) is a member of the solute carrier transporter proteins. GLUT3 has a high affinity for D-glucose and regulates glucose uptake in the neurons, as well as other tissues. Herein, we show that GLUT3 is involved in the uptake of arsenite, and its level is regulated by peroxiredoxin 1 (PRDX1). In the absence of PRDX1, GLUT3 mRNA and protein expression levels are low, but they are increased upon arsenite treatment, correlating with an increased uptake of glucose. The downregulation of GLUT3 by siRNA or deletion of the gene by CRISPR cas-9 confers resistance to arsenite. Additionally, the overexpression of GLUT3 sensitises the cells to arsenite. We further show that GLUT3 interacts with PRDX1, and it forms nuclear foci, which are redistributed upon arsenite exposure, as revealed by immunofluorescence analysis. We propose that GLUT3 plays a role in mediating the uptake of arsenite into cells, and its homeostatic and redox states are tightly regulated by PRDX1. As such, GLUT3 and PRDX1 are likely to be novel targets for arsenite-based cancer therapy. Other Information Published in: Cells License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/cells12232682